Plant Disease Prediction using Machine Learning - Vivek Kumar Soni, Prerna Soni (Mathematical Statistician and Engineering Applications, 2023)
The major population of Indians is relies on agriculture. The production of crop and income and yield are directly affected by plant diseases. Prediction of plant diseases is very important step to arrest the loss so researchers are included for such a mechanism which can overcome this problem with the modern approaches of science like machine learning techniques. The present paper includes collection of leaf randomly with healthy and diseased leaf and identifying those leaves using prepared data sets. It involves CNN Convolution Neural Network which will be able to predict whether a plant is suffering from a disease or not. The proposed paper uses different layers and other hyperparameters for building, training and testing this classification model.